Cost Analysis of a School-Based Social and Emotional Learning and Literacy Intervention1. Issue 3 (10th April 2015) - Long, Katherine; Brown, Joshua L.; Jones, Stephanie M.; Aber, J. Lawrence; Yates, Brian T.
Abstract : Purpose : There is limited research on the costs of social and emotional learning (SEL) interventions [Crowley, Jones, Greenberg, Feinberg & Spoth (2012). Resource Consumption of a Diffusion Model for Prevention Programs: The PROSPER Delivery System. Journal of Adolescent Health, 50 (3), 256–263]. This paper describes a comprehensive methodology for determining the costs of a successful universal, school-based SEL intervention that was implemented in nine public schools over 3 years. Methods : Resource costs were identified using the Cost–Procedure–Process–Outcome Analysis Model [Yates (1996). Analyzing Costs, Procedures, Processes, and Outcomes in Human Services. Thousand Oaks, CA, US: Sage Publications, Inc.; Yates (1999). Measuring and Improving Cost, Cost-Effectiveness, and Cost-Benefit for Substance Abuse Treatment Programs . No. NIH 99-4518, 135] and the ingredients model [Levin (Ed.) (1983). Cost-Effectiveness A Primer (Vol. 4). Beverly Hills, CA: Sage; Levin & McEwan (2001). Cost-Effectiveness Analysis: Methods and Applications . (2nd ed.). Thousand Oaks, CA: Sage Publications]. This involved careful identification of resource use, finding the cost per unit for each resource by intervention activity, and ultimately calculating the total resource cost (resource use × cost per unit). Results : Our analysis estimated the overall cost of this 3-year SEL and literacy intervention to be 1, 831, 296 for nine schools. This averages to 67, 825 yearly per school and 130 yearly for each student. The analysis estimated the first year of the intervention to be the costliest (683, 106) and then decreasing in Year 2 (581, 764) and Year 3 (566, 426). Conclusion : This research emphasizes the need to study the costs of SEL interventions. By providing a detailed and standardized methodology, this cost analysis can provide added support for implementing an effective social and emotional learning intervention in a school setting. Furthermore, it provides groundwork for more advanced cost analyses, such as a cost–effectiveness analysis or a benefit-cost analysis (BCA).